Brandons - Thirkell, Angela (London Virago, 2014)
The Brandons cheerfully confront matters of love, money, and an ill-tempered dowager aunt Lavinia Brandon is quite the loveliest widow in Barsetshire, blessed with beauty and grace, as well as two handsome grown-up children, Delia and Francis. So thinks their cousin Hilary Grant when he comes to stay and--like many before him--promptly falls for his fragrant hostess. Meanwhile, the Brandons' ill-tempered dowager aunt is stirring up controversy over her legacy, and Lavinia's attention is further occupied by the challenges of making a match between the vicar and gifted village help meet Miss Morris, and elegantly deterring her love-struck suitors.
108535
Keywords: Inheritance and succession -- Fiction; Country life -- Fiction; Fiction